2007
DOI: 10.3174/ajnr.a0638
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of High-Resolution MR Imaging in Giant Cell Arteritis

Abstract: BACKGROUND AND PURPOSE:Clinical indications of giant cell arteritis may be unspecific, and noninvasive diagnosis is often difficult. This study investigated the hypothesis that high-resolution MR imaging of the superficial cranial arteries is a noninvasive imaging technique that can detect the occurrence of giant cell arteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(99 citation statements)
references
References 24 publications
5
82
0
12
Order By: Relevance
“…A sensitivity of 0.80 and a specificity of 0.80 for the detection of GCA by using this imaging protocol were comparable with recent studies with reported values of sensitivities between 0.80% and 0.85% and specificities ranging from 0.71% to 0.95%. 7,17 This result might be accounted for by the differing number of days that patients received corticosteroids before MR imaging examination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A sensitivity of 0.80 and a specificity of 0.80 for the detection of GCA by using this imaging protocol were comparable with recent studies with reported values of sensitivities between 0.80% and 0.85% and specificities ranging from 0.71% to 0.95%. 7,17 This result might be accounted for by the differing number of days that patients received corticosteroids before MR imaging examination.…”
Section: Discussionmentioning
confidence: 99%
“…So far, larger studies focusing on GCA have not reported involvement of any intradural arteries. 7,8,10,11,14 This discrepancy might be caused by the differing study designs and MR imaging protocols that are typically based on the focus of the study. In general, deferring sequence parameters optimized for visualization of mural inflammation of intra-and extracranial vessels are mandatory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In giant cell vasculitis, inflammation may exclusively involve great blood vessels, which are unavailable to echosonography and biopsy. Therefore, magnetic resonance imaging (MRI) has a major role in the diagnosis of inflammatory lesions in major arterial walls as well as in the follow-up of therapeutic efficacy (2)(3)(4). MRI is also the method of choice in the follow-up of possible complications of inflammatory events in the aortic wall, e.g., aneurysms and dissection (4).…”
Section: Introductionmentioning
confidence: 99%